Accelerated preconditioning Krasnosel'skiĭ-Mann method for efficiently solving monotone inclusion problems - Artsawang, Natthaphon (AIMS mathematics, 2023)
In this article, we propose a strongly convergent preconditioning method for finding a zero of the sum of two monotone operators. The proposed method combines a preconditioning approach with the robustness of the Krasnosel'skiĭ-Mann method. We show the strong convergence result of the sequence generated by the proposed method to a solution of the monotone inclusion problem. Finally, we provide numerical experiments on the convex minimization problem.